The Federal Reserve's role in the global economy : a historical perspective - Bordo, Michael D.; Wynne, Mark A. (Studies in macroeconomic history)
"The importance of international considerations in the US Federal Reserve System's deliberations has become more and more important over time as global financial crises and events create ever stronger repercussions in the US economy. This book critically evaluates the role of the Federal Reserve System as a player in the international monetary system over the past 100 years, starting with its initial responsibility under the gold standard and looking ahead to the challenges it will face in the twenty-first century under the fiat standard. The book is based on a conference of the same name held at the Federal Reserve Bank of Dallas in September 2014, as part of the Federal Reserve System's centennial, and contributors include many of the most highly regarded financial historians and policymakers"--